One step strategy for reduced graphene oxide/cobalt-iron oxide/polypyrrole nanocomposite preparation for high performance supercapacitor electrodes. (20th September 2022) - Ishaq, Saira; Moussa, Mahmoud; Kanwal, Farah; Ayub, Raheel; Van, Truc Ngo; Azhar, Umar; Losic, Dusan
Abstract: Supercapacitors are crucial energy generating devices due to profound characteristics namely high specific capacitance, rapid charge storing capability, high discharge time, and environmentally friendly nature. Supercapacitors have high power density but they have demerits of low energy density; usually less than 10 Whkg −1, which needs to be improved to make supercapacitors excellent energy storage devices. Aim of the present research was to fabricate supercapacitor electrodes with high energy density. To achieve these goals herein is presented a simple one step strategy to synthesize binary composite of reduced graphene oxide (rGO) and cobalt-iron oxide (rGO/CoFe2 O4 ) using urea. Urea is used not only to reduced GO but also assist in formation of cobalt-iron oxide from its reactants thus forming binary rGO/CoFe2 O4 nanocomposite which was further used to make electrodes for supercapacitors. Synthesized rGO/CoFe2 O4 electrode exhibited gravimetric capacitance of 97 Fg −1 while areal capacitance was 165 mFcm −2, when measured at 5 mVs −1 . To further enhance electrochemical performance a ternary composite namely reduced graphene oxide/cobalt-iron oxide/polypyrrole (rGO/CoFe2 O4 /PPy) was synthesized by adding polypyrrole (PPy). Both gravimetric and areal capacitances of the rGO/CoFe2 O4 /PPy were improved to 164 Fg −1 and 279 mFcm −2, respectively. Specific energy and specific power of our synthesized ternary rGO/CoFe2 O4 /PPy nanocomposite were 22.8 Whkg −1 and 410 Wkg −1, respectively. Results from this study showed a simple fabrication method of binary and ternary nanocomposites and synergistic influence of participating components on electrode performance for supercapacitors exhibiting high gravimetric and areal capacitances, as well as high energy and power densities.